Laparoscopic reduction and repair of a left paraduodenal hernia. Issue 12 (15th December 2019) - Sakamoto, Takashi; Lefor, Alan Kawarai
Abstract : Left paraduodenal hernias are the most common type of congenital internal hernia, but they are difficult to diagnose without appropriate imaging. A 79-year-old man with a history of recurrent abdominal pain had another similar episode of abdominal pain, which prompted him to seek evaluation. The pain resolved spontaneously on arrival to the hospital. Enhanced CT scan showed the characteristic findings of a left paraduodenal hernia and laparoscopic repair was undertaken. The small intestine was reduced successfully, and the hernia orifice was approximated with a continuous closure. He was discharged uneventfully 4 days after admission. The characteristic clinical and imaging findings of paraduodenal hernias are reviewed. Laparoscopic repair is reasonable in patients who have a paraduodenal hernia without intestinal ischemia.